SCREENING OF TOMATO GENOTYPES AGAINST EARLY BLIGHT (ALTERNARIA SOLANI) UNDER FIELD CONDITION - SUNIL KUMAR; KARTIKEYA SRIVASTAVA (The Bioscan, 2013)
Early blight (Alternaria solani) of the tomato is most destructive disease in tropical and subtropical countries. In natural epidemics of early blight are strongly inûuenced by environmental conditions, even though severe disease appears every year in northern India. If indices were available to evaluate resistance in breeding materials, breeding programs could be more efficient. Leaf blight, stem blight and apical fruit rot are the most damaging symptoms of the disease and can cause complete loss of the crop when severe. Forty four tomato genotypes were used in this study to differentiate between early blight resistant and susceptible genotypes selected to represent a range of reactions when screened under field condition. Evaluation was conducted in replicated trials under field conditions in two Rabi seasons 2010 and 2011 at vegetable research farm of Banaras Hindu University, Varanasi India. Plants were evaluated for disease symptoms, area under the Percent disease Index (PDI) and area under the diseases progress curve. The highest early blight disease incidence was found in PS-1(73.56%), Kashi Amrit (71.12%), Fla-7171(69.69%), H-T-4 (61.26%), DT-10 (53.65%) and the lowest in H-88-74-1(12.04%), EC- 520061(12.29%) and EC-521071 (25.00%) Floraded (27.00%) and Swarna Naveen (28.61%). Other fifteen genotypes showed moderately resistant and twenty genotypes showed susceptible but two genotypes were found highly resistant on the basis of early blight disease intensity in 2010 and semilar result also found in 2011.